ASSESSING PERCEPTION AND ACTION OF PARENTS, TEACHERS, AND SCHOOL LEADERS ON SCHOOL READINESS. A CASE OF MTWARA REGION-TANZANIA - Ibrahim Emilly Nzunda; Euis Kurniati (Universitas Muhammadiyah Semarang, 2021)
School readiness as a concept has been there for a long period of time but has gained attention in the last few years. The perception of parents, teachers and school leaders on school readiness are very important to determine the extent to which children are ready to enter in the school setting. Therefore, this study specifically examines the perceptions and actions of parents, teachers, and school leaders on school readiness and how they contribute to the smooth transformation of children into school settings in Mtwara Region-Tanzania. However, many studies have been done on school readiness and many of them focused much on educational result oriented rather that system and mechanical oriented. Furthermore, this research has used qualitative methods such as online survey (interview, questionnaire and web search), document analysis. The result of this findings demonstrates that there is a need of the government intervention toward understanding of school readiness to parents, teachers, and school leaders. 70 percent of the teachers, parents and school leaders are not aware of the learning autonomous, therefore through this study the government should start to formulate and implement learning autonomous and online studies particularly in tragedy pandemic era such as Covid-19. Key words: school readiness; perceptions; childhood; learning autonomous; Tanzania.